The Concentrations of Fatty Acids, Cholesterol and Vitamin E in Cooked Longissimus, Semitendinosus, Psoas Major and Supraspinatus Muscles from Cattle Offered Grass Only, Concentrates Ad Libitum or Grass Silage Supplemented with Concentrates - Aidan P. Moloney; Cormac McElhinney; Raquel Cama-Moncunill; Edward G. O′Riordan; Frank J. Monahan (Foods)
There is growing interest among consumers in the nutritional value of the food they consume. The objectives of this study were (1) to document the nutritional value, with a focus on the fatty acid profile, of beef from cattle from one commercial production system that only ever received grass-based feed ingredients compared with similar animals finished in more conventional, i.e., with high-concentrate or concentrate-supplemented grass silage, production systems; (2) to determine the effect of the dietary treatments on muscles representing a range in intramuscular fat concentrations and commercial value, viz supraspinatus, semitendinosus, longissimus lumborum and psoas major; and (3) to determine if the fatty acid profile can be used to distinguish between different beef muscles. Dietary treatment and muscle type influenced the concentration of omega-3 polyunsaturated fatty acids and conjugated linoleic acid, with the highest concentrations observed in psoas major from cattle fed grass only. These data should be of use to the meat industry and to those updating nutritional databases. The possibility of discriminating beef according to its dietary background based on the fatty acid profile was confirmed. While this approach was moderately successful with respect to the separation of supraspinatus, longissimus lumborum and psoas major, discrimination between the more valuable longissimus lumborum and the lower-value semitendinosus is more challenging.